Wave pattern motion and stick–slip limit cycle oscillation of a disc brake - Kang, Jaeyoung; Krousgrill, Charles M.; Sadeghi, Farshid (Journal of sound and vibration, 2009)
This paper examines the dynamic response of a rotating squealing disc brake subject to distributed nonlinear contact stresses where two brake pads are assumed to be stationary and rigid. The friction stresses produce high-frequency vibrations that exhibit standing or traveling waves on the disc surface. The wave pattern resulting from the binary flutter mechanism of one transverse doublet mode pair is studied here. The results show that the wave pattern is associated with mode-coupling character. For a steady-squealing mode, the stick zone of the contact area is determined by a smooth friction–velocity curve having both negative and positive slopes.